A Planar Reconfigurable Radiation Pattern Dipole Antenna with Reflectors and Directors for Wireless Communication Applications - Imen Ben Trad; Jean Marie Floc’h; Hatem Rmili; M’hamed Drissi; Fethi Choubani (International Journal of Antennas and Propagation)
A planar printed dipole antenna with reflectors and directors, able to steer its radiation pattern in different directions, is proposed for telecommunication applications. Starting from a dual-beam printed dipole antenna achieved by combining two elementary dipoles back to back, and by loading four PIN diodes, three modes of reconfigurable radiation patterns are achieved at the frequency 2.56 GHz thanks to switches states. A prototype of the structure was realized and characterized; an efficiency of 75% is obtained. Simulation and measured results of the results are presented and discussed.